Biomass potiential enegry from agricultural wastes - Nurul Hayati, Jamil (Universiti Malaysia Sarawak (UNIMAS), 2004)
This project is about biomass potential energy from agricultural wastes. The focus is on Sarawak agricultural activities where the study begins with recognizing the potential agricultural resources in this state. The main objectives of this project is to determine the relation between energy content and moisture content in the potential biomass resources.